Synapse-Associated Protein 97 Regulates the Membrane Properties of Fast-Spiking Parvalbumin Interneurons in the Visual Cortex - Akgul, Gulcan (Society for Neuroscience, 2013)
Fast-spiking parvalbumin (PV)-positive interneurons in layers 2/3 of the visual cortex regulate gain control and tuning of visual processing. Synapse-associated protein 97 (SAP97) belongs to a family of proteins that have been implicated in regulating glutamatergic synaptic transmission at pyramidal-to-pyramidal connections in the nervous system. For PV interneurons in mouse visual cortex, the expression of SAP97 is developmentally regulated, being expressed in almost all juvenile but only a fraction, ∼40%, of adult PV interneurons. Using whole-cell patch-clamping, single-cell RT-PCR to assay endogenous expression of SAP97 and exogenous expression of SAP97, we investigated the functional significance of SAP97 in PV interneurons in layers 2/3 of the visual cortex. PV interneurons expressing SAP97, either endogenously or via exogenous expression, showed distinct membrane properties from those not expressing SAP97. This included an overall decrease in membrane excitability, as indexed by a decrease in membrane resistance and an increase in the stimulus threshold for the first action potential firing. Additionally, SAP97-expressing PV interneurons fired action potentials more frequently and, at moderate stimulus intensities, showed irregular or stuttering firing patterns. Furthermore, SAP97-expressing PV interneurons showed increased glutamatergic input and more extensive dendritic branching when compared with non-expressing PV interneurons. These differences in membrane and synaptic properties would significantly alter how PV interneurons expressing SAP97 compared with those not expressing SAP97 would function in local networks. Thus, our results indicate that the scaffolding protein SAP97 is a critical molecular factor regulating the input–output relationships of cortical PV interneurons.